Boehmite derived surface functionalized carbon nanotube-reinforced macroporous alumina ceramics - Zaman, Ali Can; Ustundag, Cem B.; Kaya, Cengiz (ELSEVIER SCI LTD, 2010)
Carbon nanotube (CNT)-reinforced macroporous alumina ceramics with tailored porosity were fabricated using hydrothermally synthesized (200 degrees C for 2 h) boehmite CNT starting composite powders. Multi-wall CNTs were first mixed with a mixture of chemicals suitable to synthesize stoichiometric boehmite powders and then put in an autoclave. During hydrothermal synthesis, the formation of fine particles of boehmite was accompanied by the functionalization of CNTs. Subsequently, CNT boehmite powders were used to produce bulk ceramics and sintering took place in a vacuum furnace at 1450 degrees C for 3h for the formation of CNT-reinforced alumina ceramics. The pore network in various dimensions occurred as a consequence of the reconstructive transformation and dehydration of boehmite during the transformation to alumina. FEG-SEM and TEM analysis were used to determine the CNT distribution in the matrix, the morphology and size of particles, as well as the visual properties of the pores. The final macroporous alumina ceramics can be considered to be ideal for the separation and filtration of contaminants in liquid or air environment. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Al2O3; Carbon nanotube; Nanocomposites; Porous ceramics; REMOVAL; Materials Science